Bahasa Inggris - Rahmadi Agus Setiawan (At Turots: Jurnal Pendidikan Islam, 2026)
The construction sector in Indonesia faces an ethical crisis spanning structural failures that endanger life, pervasive corruption, and ecological degradation, problems that are fundamentally moral rather than merely technical. Islamic Religious Education (PAI) in public universities is institutionally positioned to address this crisis, yet in engineering faculties it remains normative-textual and epistemologically isolated from students' technical disciplines. This study aims to reconstruct an integrated PAI-STEAM curriculum for civil engineering programs by operationalizing the maqāshid al-sharīʿa as an ethics of infrastructure engineering aligned with global accreditation standards. Employing qualitative library research with a philosophical-hermeneutic approach, the study analyzes Islamic juridical sources and engineering-accreditation documents through transdisciplinary content analysis and creative synthesis. The study yields three principal results. First, integration requires dissolving the dichotomy of knowledge at the epistemological level, repositioning engineering laws as sunnat Allāh and the STEAM "Arts" component as an axiological gateway for ethical values. Second, the five maqāshid pillars (hifdz al-nafs, hifdz al-bīʾah, hifdz al-māl, hifdz al-ʿaql, and hifdz al-dīn) map onto assessable engineering domains that correspond directly to IABEE accreditation criteria, consolidated in a Complementarity Matrix. Third, an Integrated Project-Based Learning model (IPBL-OBE), anchored in a Green Eco-Mosque capstone project, translates these correspondences into measurable graduate outcomes. The study contributes a novel epistemological framework and a ready curriculum template, repositioning PAI from an accreditation-neutral formality into a substantive accreditation asset. The proposed framework is intended to serve as a practical reference for curriculum developers, PAI lecturers, and engineering faculty seeking to design accreditation-aligned, values-based learning experiences, while acknowledging that its pedagogical claims await empirical validation.